Literature Review: Implementation of Patient Safety Goals in Hospitals in Indonesia - Andryani Larasati; Inge Dhamanti (Media Gizi Kesmas, 2021)
Background: The implementation of a good patient safety system in the hospital aims to minimize and prevent patient safety incidents. The patient safety goals is a system that aims to encourage specific improvements in patient safety. Patient safety goals are actions that must be taken by the hospital to prevent patient safety incidents that can harm patients and the hospital. Purpose: Writing this review article aims to provide an overview of the implementation of patient safety goals in hospitals in Indonesia.Methods: The method used in this article is a literature review. Article searches were conducted through Google Scholar and Portal Garuda with the keywords "patient safety goals", "hospitals", and "Indonesia". Results: The total findings of the articles were 738, but only 11 articles matched the inclusion criteria. Based on 11 articles analyzed, only 2 articles showed that the implementation of all points in the patient safety goals in the hospital had reached the target and were in accordance with the standard. Conclusion: Low compliance of officers, unsupportive facilities and infrastructure, and low management commitment are some of the factors that have not yet optimalized the implementation of patient safety goals in the hospital. Therefore, it is necessary to improve technical assistance, supervision, and support for adequate facilities and infrastructure.Keywords: patient safety goals, patient safety incidents, hospital.